Computational finance acceleration using CUDA on graphics processing units - Kanoria, Kanishk (2014)
The computation of fair prices for options has become an increasingly intrinsic aspect of finance today. In an era of supercomputing, there is a demand to perform calculations quicker and achieve accurate results to complex problems like